Ceftazidime and cefepime antagonize 5-fluorouracil’s effect in colon cancer cells - Christina Pfab; Anush Abgaryan; Barbara Danzer; Fatme Mourtada; Weaam Ali; André Gessner; Nahed El-Najjar (BMC Cancer, 2022)
Abstract Background Drug-drug interaction (DDI), which can occur at the pharmacokinetics and/or the pharmacodynamics (PD) levels, can increase or decrease the therapeutic or adverse response of a drug itself or a combination of drugs. Cancer patients often receive, along their antineoplastic agents, antibiotics such as ß-lactams to treat or prevent infection. Despite the narrow therapeutic indices of antibiotics and antineoplastic agents, data about their potential interaction are insufficient. 5-fluorouracil (5-FU), widely used against colon cancer, is known for its toxicity and large intra- and inter- individual variability. Therefore, knowledge about its interaction with antibiotics is crucial. Methods In this study, we evaluated at the PD levels, against HCT-116 colon cancer cells, DDI between 5-FU and several ß-lactams (ampicillin, benzypenicillin, piperacillin, meropenem, flucloxacillin, ceftazidime (CFT), and cefepime (CFP)), widely used in intensive care units. All drugs were tested at clinically achieved concentrations. MTT assay was used to measure the metabolic activity of the cells. Cell cycle profile and apoptosis induction were monitored, in HCT-116 and DLD-1 cells, using propidium iodide staining and Caspase-3/7 activity assay. The uptake of CFT and CFP by the cells was measured using LC-MS/MS method. Results Our data indicate that despite their limited uptake by the cells, CFT and CFP (two cephalosporins) antagonized significantly 5-FU-induced S-phase arrest (DLD-1 cells) and apoptosis induction (HCT-116 cells). Remarkably, while CFP did not affect the proliferation of colon cancer cells, CFT inhibited, at clinically relevant concentrations, the proliferation of DLD-1 cells via apoptosis induction, as evidenced by an increase in caspase 3/7 activation. Unexpectedly, 5-FU also antagonized CFT’s induced cell death in DLD-1 cells. Conclusion This study shows that CFP and CFT have adverse effects on 5-FU’s action while CFT is a potent anticancer agent that inhibits DLD-1 cells by inducing apoptotic cell death. Further studies are needed to decipher the mechanism(s) responsible for CFT’s effects against colon cancer as well as the observed antagonism between CFT, CFP, and 5-FU with the ultimate aim of translating the findings to the clinical settings.